Variation in the Essential Oil Composition and Antimicrobial Activity of Baccharis spartioides (H. et A.) J. Rimy from Three Regions of Argentina. - Oliva, Maria de Las Mercedes (2007)
Hydrodistilled oils of Baccharis spartioides from three populations of Argentina (Northwest, Central and Patagonia areas) were analyzed by using GC and GC/MS. Thirty-nine compounds were identified in the oils and a relatively high variation in their contents and in their antimicrobial activity was found. The main constituents of the oils were camphor (26.5–50%), limonene (4.3–35.8%), citronellal (12%), carvone (10%) and spathulenol (2.1–11.8%). The oil was tested against ten Gram-positive and Gram-negative bacteria and against the yeast Candida albicans. The best antimicrobial activity of the oils of B. spartioides was against S. aureus and B. cereus while P. aeruginosa was the most resistant bacteria to all the oils.